The impact of COVID-19 on rheumatology training—results from the COVID-19 Global Rheumatology Alliance trainee survey. Issue 1 (21st February 2022) - Young, Kristen; Yeoh, Su-Ann; Putman, Michael; Sattui, Sebastian; Conway, Richard; Graef, Elizabeth; Kilian, Adam; Konig, Maximilian; Sparks, Jeffrey; Ugarte-Gil, Manuel; Upton, Laura; Berenbaum, Francis; et al.
Abstract: Objective: The aim was to evaluate the impact of the coronavirus disease 2019 (COVID-19) pandemic on the clinical experiences, research opportunities and well-being of rheumatology trainees. Methods: A voluntary, anonymous, Web-based survey was administered in English, Spanish or French from 19 August 2020 to 5 October 2020. Adult and paediatric rheumatology trainees were invited to participate via social media and email. Using multiple-choice questions and Likert scales, the perceptions of trainees regarding the impact of the COVID-19 pandemic on patient care and redeployment, learning and supervision, research and well-being were assessed. Results: There were 302 respondents from 33 countries, with 83% in adult rheumatology training. An increase in non-rheumatology clinical work was reported by 45%, with 68% of these having been redeployed to COVID-19. Overall, trainees reported a negative impact on their learning opportunities during rheumatology training, including outpatient clinics (79%), inpatient consultations (59%), didactic teaching (55%), procedures (53%), teaching opportunities (52%) and ultrasonography (36%). Impacts on research experiences were reported by 46% of respondents, with 39% of these reporting that COVID-19 negatively affected their ability to continue their pre-pandemic research. Burnout and increases in stress were reported by 50% and 68%, respectively. Physical health was negatively impacted by training programme changes in 25% of respondents. Conclusion: The COVID-19 pandemic has had a substantial impact on rheumatology training and trainee well-being. Our study highlights the extent of this impact on research opportunities and clinical care, which are highly relevant to future curriculum planning and the clinical learning environment.